2021
DOI: 10.1002/cssc.202100511
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Talk‐Suppressing Electrolyte Additive Enabling High Voltage Performance of Ni‐Rich Layered Oxides in Li‐Ion Batteries

Abstract: Control of electrode-electrolyte interfacial reactivity at highvoltage is a key to successfully obtain high-energy-density lithium-ion batteries. In this study, 2-aminoethyldiphenyl borate (AEDB) is investigated as a multifunctional electrolyte additive in stabilizing surface and bulk of both Ni-rich Li-Ni 0.85 Co 0.1 Mn 0.05 O 2 (NCM851005) and graphite electrodes in a cell operated with elevated upper cutoff voltage of 4.4 V vs. Li + /Li. The presence of AEDB in a full-cell inhibits structural degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 75 publications
1
21
0
Order By: Relevance
“…Such compounds added to the electrolyte, typically in concentrations of <10 %, are often designed to improve interfacial chemistry. [109][110][111][112][113] The role of tris(trimethylsilyl) phosphite (TMSPi) as an electrolyte additive to improve the electrochemical performance of NMC811/Si-Graphite cells was investigated by synchrotron-based XPS depth profiling. 114 The morphological and compositional differences of the CEI and SEI were probed for the cathode and anode, respectively.…”
Section: Structure Composition and Formation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such compounds added to the electrolyte, typically in concentrations of <10 %, are often designed to improve interfacial chemistry. [109][110][111][112][113] The role of tris(trimethylsilyl) phosphite (TMSPi) as an electrolyte additive to improve the electrochemical performance of NMC811/Si-Graphite cells was investigated by synchrotron-based XPS depth profiling. 114 The morphological and compositional differences of the CEI and SEI were probed for the cathode and anode, respectively.…”
Section: Structure Composition and Formation Mechanismsmentioning
confidence: 99%
“…Such compounds added to the electrolyte, typically in concentrations of <10%, are often designed to improve interfacial chemistry. 109–113…”
Section: The Electrode–electrolyte Interfacementioning
confidence: 99%
“…Based on this mechanism, the MTE-TMS additive causes an improvement in cycling performance and coulombic efficiency. Pham et al [ 11 ] reported 2-aminoethyl diphenyl borate (AEDB) as a multifunctional electrolyte additive for improving the electrochemical properties of the battery. AEDB possesses a special chemical structure for relieving surface degradation reactions.…”
Section: Modificationsmentioning
confidence: 99%
“…Furthermore, the cathode materials serve as the provider of lithium-ions, which greatly determines the capacity of LIBs. Nowadays, a great deal of research work has been done to develop cathode materials with superior specific capacities at high operating voltage [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 So far, one of the main ways to achieve the ultrahigh energy density of LIBs has been to increase the operating voltages (44.3 V) in the state-of-art batteries. [3][4][5] However, the actual application of high-voltage LIBs still faces some formidable obstacles, i.e., the adverse reactions at the interfaces between electrodes and liquid electrolytes, in particular for the Ni-rich LIBs at extremely high temperatures. [6][7][8] However, the solid electrolyte interphase (SEI) on the surfaces of electrodes, which originally play an important role in interfacial protective layers, is continuously damaged and regrows at high potentials during the chargedischarge cycling.…”
Section: Introductionmentioning
confidence: 99%